Intraspecific phenotypic variation in deer: the role of genetic and epigenetic processes - Fluck, Werner Thomas (2011)
Intraspecific phenotypic variation (PV) in deer is common, at times impressively diverse, and involvesmorphology, development, physiology, and behaviour. Until recently considered a nuisance in evolutionary andtaxonomic studies, PV has become the primary target to study fossil and extant species. Phenotypes are traditionallyinterpreted to express primarily interactions of inherited genetic variants. PV certainly originates from different genotypes,but additional PV, referred to as phenotypic plasticity (PP), results from gene expression responsive to environmentalconditions and other epigenetic factors. Usage of ‘epigenetics’ for PP has increased exponentially with 20 316 publishedpapers (Web-of-Science 1990 – May 2010), yet it does not include a single paper on cervids (1900 to the present). During the‘genomic era’, the focus was on the primaryDNAsequences and variability therein. Recently however, several higher orderarchitectural genomic features were detected which all affect PV.(1) Genes: poli-genic traits; pleiotropic genes; poli-allelic genes; gene dosage (copy number variants, CNV); singlenucleotide variance in coding and gene regulatory regions; mtDNA recombinations and paternal mtDNA inheritance.(2) Gene products: pleiotropic gene products; multiple protein structures through alternative splicing; variable geneproduct reactions due to gene dosage.(3) Gene expression: (i) epigenetic regulation at the DNA, nucleosomal and chromosomal levels; (ii) large-scalegenomic structural variation (i.e. CNV imbalance); (iii) transcription factor proteins (TF), each regulating up to 500 targetgenes, with TF activity varying 7.5–25% among individual humans (exceeding variation in coding DNA by 300–1000·);(iv) non-protein-coding RNA (98.5% of genome) constituting maybe hundreds of thousands RNA signals; (v) geneexpression responsive to external and internal environmental variation; (vi) transgenerational epigenetic inheritance (e.g.from ubiquitous non-gametic interactions, genomic imprinting, epistasis, transgenerational gene–diet interactions);(vii) epigenetic stochasticity resulting in random PP. A unique example of labile traits in mammals is the yearlyregrowth of a complete appendage, the antler in cervids.Highly complex assortments of genotypes lead to a spectrum of phenotypes, yet the same spectrum can result if a singlegenotype generates highly complex assortments of epigenotypes. AlthoughDNAis the template for theDNA–RNA–proteinparadigm of heredity, it is the coordination and regulation of gene expression that results in wide complexity and diversityseen among individual deer, and per-generation variety of phenotypes available for selection are greater than availablegenotypes. In conclusion, epigenetic processes have fundamental influences on the great intraspecific PV found in deer,which is reflected in broad ranges of environmental conditions under which they can persist. Deer management andconservation of endangered cervids will benefit from appreciating the large inherent PV among individuals and the immensecontribution of epigenetics in all aspects of deer biology and ecology.